Experimental diagenesis using present-day submarine turbidite sands - Bello, Abdulwahab Muhammad; Charlaftis, Dimitrios; Jones, Stuart J.; Gluyas, Jon; Acikalin, Sanem; Cartigny, Matthieu; Al-Ramadan, Khalid (Frontiers in Earth Science, 2022)
Hydrothermal-reactor experiments were conducted to investigate the potential formation of chlorite and microquartz grain coatings on detrital quartz and feldspar grains, and to understand their role in inhibiting the formation of quartz cement and feldspar (albite) overgrowths. Modern-day, proximal and distal unconsolidated sediment from the Bute Inlet (British Columbia, Canada) were used as starting material, with known amount of precursor clay content. The samples were heated to 250 ◦C at water vapour pressure in a hydrothermal reactor for 72 hours. The experiments were performed with and without a silica supersaturated Na2CO3 (0.1 M) solution. Detailed microscopy and EDS mapping analysis identified that the main chlorite precursor, crucial for the formation of the synthesized grain coatings, was a Mg-rich chlorite. The experimental results showed that where the volume of precursor chlorite was low (i.e., 0.1 %), notably in the proximal channel Bute samples, chlorite coatings were poorly developed, with a clay volume and maximum chlorite-coating coverage of 0.23 % and 47 %, respectively. In contrast, with an initial precursor chlorite volume of 6 %, the distal lobe Bute sample has generated chlorite volume ranging from 19 to 27 % post-experiment, with a maximum chlorite-coating coverage of 77 %. The chlorite and microquartz coatings produced in the study are morphologically and compositionally akin to those occurring in natural sandstone reservoir, and have inhibited the formation of quartz and albite cementation. The results provide quantitative data that can be used as inputs for modelling diagenetic alterations in mesodiagenetic environments.